Human T‐lymphotropic virus type I proviral loads in patients with adult T‐cell leukemia–lymphoma: Comparison between cutaneous type and other subtypes. Issue 12 (30th June 2015) - Yonekura, Kentaro; Utsunomiya, Atae; Seto, Masao; Takatsuka, Yoshifusa; Takeuchi, Shogo; Tokunaga, Masahito; Kubota, Ayumu; Takeda, Koichiro; Kanzaki, Tamotsu; Uchida, Youhei; Kawai, Kazuhiro; Kanekura, Takuro
Abstract: Adult T‐cell leukemia–lymphoma (ATL), characterized by various clinicopathological features, is divided into four clinical subtypes, namely, acute, lymphoma, chronic and smoldering types, and the treatment strategy differs according to the clinical subtype. The designation cutaneous type ATL has been proposed to describe a peculiar subgroup of smoldering type ATL in which the skin is predominantly affected. However, diagnostic criteria and prognostic factors for cutaneous type ATL remain to be determined. Therefore, we performed a retrospective study to obtain a precise method for subtype classification and to clearly define cutaneous type ATL. A total of 87 ATL patients (acute, n = 31; lymphoma, n = 6; chronic, n = 24; smoldering, n = 26) were enrolled. The human T‐lymphotropic virus type I (HTLV‐1) proviral load in peripheral blood and the serum soluble interleukin‐2 receptor (sIL‐2R) level were evaluated with respect to the clinical features of the different types of ATL. The HTLV‐1 proviral load was significantly increased in the acute and chronic type and the serum sIL‐2R level was increased in the acute and lymphoma type. The HTLV‐1 proviral load was significantly lower in cutaneous than other smoldering types of ATL without skin lesions. The clinical findings of cutaneous type ATL were also different from other subtypes. These results indicate that, in combination, determination of the HTLV‐1 proviral load and the serum sIL‐2R level is useful for distinguishing among the different types of ATL, and strongly suggest that cutaneous type ATL is a distinct clinical entity.